Enhancing Interpretability of Patient-Reported Outcomes Measurement Information System (PROMIS) and Related Measures in Rehabilitation Populations: A Systematic Review of Clinical and Research Applications. - Alhasani, Rehab; Ataman, Rebecca; Nafees, Zanib; Luong, Anita; Auneau-Enjalber, Line; Quigley, Adria; Michael, Henry Ukachukwu; Ahmed, Sara (Archives of Physical Medicine & Rehabilitation, 2026)
To evaluate and synthesize interpretability metrics, including minimal important change (MIC), minimal important difference (MID), and minimal detectable change (MDC), across Patient-Reported Outcomes Measurement Information System (PROMIS) and related systems (Quality of Life in Neurological Disorders [Neuro-QoL], Quality of Life in Traumatic Brain Injury [TBI-QoL], Quality of Life in Spinal Cord Injury [SCI-QoL]) in rehabilitation populations. Comprehensive searches of electronic databases (MEDLINE, EMBASE, PsycINFO, HaPI, CINAHL, Cochrane Library, Web of Science) and clinical trial registries (ISRCTN Registry, ClinicalTrials.gov) were conducted from inception through March 23, 2024, in consultation with an information specialist. Eligible studies assessed interpretability metrics in rehabilitation populations using PROMIS, Neuro-QoL, TBI-QoL, or SCI-QoL. Studies of pediatric or nonrehabilitation populations, abstracts, posters, or consensus statements were excluded. A total of 202 studies met inclusion criteria. Two independent reviewers extracted study characteristics, interpretability metrics, and analytical methods following COnsensus-based Standards for the Selection of Health Measurement Instruments guidelines. MIC, MID, and MDC values varied widely across populations and domains. PROMIS mental health domains (eg, depression, anxiety, fatigue) demonstrated relatively consistent estimates, whereas physical function domains were more variable, particularly in chronic and geriatric groups. PROMIS Computer Adaptive Testing measures showed fewer floor and ceiling effects than short forms, indicating enhanced sensitivity to change. Limited data were available for SCI-QoL and TBI-QoL. Standardizing interpretability metrics and expanding research on SCI-QoL and TBI-QoL are critical to improving the clinical utility of these measures in rehabilitation. Future work should incorporate response-shift considerations and establish population-specific cut-points to support patient-centered care and evidence-based practice.